Genetic connectivity shapes the population structure of Puccinia polysora in the pathogen's winter-reproductive regions - Sun, Qiuyu; Gao, Jianmeng; Wang, Shuhe; Liu, Jie; Deng, Jie; Yang, Lujia; Ding, Mingliang; Da, Pu; Huang, Liqun; Shi, Junzheng; Ma, Zhanhong (Plant disease, 2025)
Southern corn rust, caused by Puccinia polysora Underw., is one of the worldwide maize disease. With the change of global climate and farming system, southern corn rust has become one of the major diseases that seriously threaten the safety of maize production in China. The disease is air-borne, and presents the regional epidemic characteristics in China; however, its population structure in different regions is still unclear. In this study, we used High-throughput sequencing techniques with a Genotyping-by-Sequencing approach to study the population structure of P. polysora in the pathogen's winter-reproductive regions. Population genetic analysis indicated that the P. polysora isolates from Ledong, Hainan, collected in July, formed a distinct genetic group, indicating seasonal genetic differentiation within this region. However, the remaining isolates from Hainan, Guangdong, and Guangxi were clustered into two main genetic groups, with no significant genetic differentiation detected among the populations from these three provinces. This suggests frequent genetic exchange among P. polysora populations in Hainan, Guangdong, and Guangxi, leading to overall genetic homogeneity. These findings underscore the role of genetic connectivity in shaping the population structure of P. polysora in the pathogen's winter-reproductive regions, offering novel insights into its genetic dynamics. Furthermore, the results provide valuable information to support the development of effective strategies for managing P. polysora in China.